Evaluation of Trichoderma spp. along with farm yard manure for the management of Fusarium wilt of cumin (Cuminum cyminum L.) - Ram Gopal, S Gangopadhyay (Journal of Spices and Aromatic Crops, 2010)
The efficacy of Trichoderma harzianum and T. viride used as seed treatment and soil applicationwith and without farm yard manure in controlling wilt of cumin (Cuminum cyminum) causedby Fusarium oxysporum f. sp. cumini was studied at Bikaner (Rajasthan) in pathogen inoculatedsoil under green house condition. The two antagonists were evaluated as seed treatment @ 4,6 and 8 g kg-1 seed; in case of soil application, these were evaluated @ 5 g kg-1 soil. Among the12 combinations tested, maximum reduction in disease incidence was recorded when T.harzianum was used as seed treatment @ 4 g kg-1 seed + soil application @ 5 g kg-1 soil alongwith soil amendment of farm yard manure @ 10 kg-1 soil. This treatment also resulted inhighest dry weight of cumin plants.